Beyond Corporate Social Responsibility : The Scope for Corporate Investment in Community Driven Development - World Bank (Washington, DC, 2012)
The last decade has witnessed expanded awareness among companies, especially multinational corporations, of their responsibilities toward the communities they impact, elaborated in the concept of Corporate Social Responsibility (CSR) and allied notions such as a Social License to Operate (SLTO). CSR is the realization of business contributions to sustainable development goals. It refers to how business takes account of its economic, social and environmental impacts in the way it operates -- maximizing the benefits and minimizing the downsides.